Developed Standard Operating Procedures for Work Discipline and Customer Service at UMKM Milan Collection - Kho, Catherine; Evi Silvana Muchsinati (Universitas Internasional Batam, 2025)
UMKM Milan Collection faced several operational problems, such as inconsistent employee discipline and different ways of serving customers because there were no written guidelines. These issues affected the daily workflow, service quality, and made it difficult for the owner to supervise employee performance. To solve these problems, the project used the PDCA (Plan–Do–Check–Act) method and carried out observations, interviews, document analysis, and direct evaluations. As a result, two important Standard Operating Procedures (SOPs) were created: the Work Discipline SOP and the Customer Service SOP. These SOPs provide clear rules for attendance, work ethics, customer interactions, handling complaints, and transaction procedures, so that all work activities become more consistent and transparent. After socializing the SOPs and implementing them on-site, the business saw many improvements. Employees became more disciplined, followed work schedules, and delivered more consistent service to customers. The owner also found it easier to supervise the team. Customers received more professional and uniform service. Overall, the results show that SOPs play an important role in improving operational efficiency, strengthening professionalism, increasing customer satisfaction, and supporting long-term stability for small businesses like Milan Collection.